Corporate governance in international new ventures and born global firms - Evers, Natasha; Gerschewski, Stephan; Khan, Zaheer; King, Tim; Kuivalainen, Olli; Puthusserry, Pushyarag (SAGE Publications, 2023)
International new ventures (INVs) and born globals (BGs) play a significant role in the global economy. These firms have rapidly expanded into foreign markets offering unique products and services. Despite the role such ventures play in the global economy, we know relatively little about the role of corporate governance (CG) in INVs and BGs and the challenges these firms face in foreign markets. This introductory article and the papers included in this Special Issue provide important insights into the role of corporate governance and the rapid rise of INVs and BGs and their evolutionary process, and highlight the topics where more research is needed. We also contribute to the current literature by examining corporate governance in early internationalising firms and discussing what sets them apart from well-established multinational enterprises.
Keywords: corporate governance; boards of directors; international new venture; born global; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|